Trajectory Tracking Composite Control for A Quadrotor UAV (International Journal of Engineering and Computer Science, 2018)
The trajectory tracking composite control scheme is proposed for quadrotor unmanned aerial vehicle (UAV) with perturbation parameters and external disturbances. Firstly, the dynamic model of quadrotor UAV is decoupled into two subsystems, which are outer loop position control system and the inner loop angle control system, respectively. Secondly, by using the interval matrices to describe the perturbation parameters, the considered control problem is transformed into robust control with uncertainties. Based on these, an effective tracking composite control strategy is proposed by combining disturbance observer control (DOBC) with H∞ control. Finally, the simulation results show the effectiveness of the proposed method.